Changes in protein fractions, trypsin inhibitor and proteolytic activity in the cotyledons of germinating chickpea - Neves, Valdir Augusto [UNESP]; Lourenço, Euclides Joaquim [UNESP] (My University, 2001)
The chickpea seed germination was carried out in 6 days. During the period it was observed a little variation on total nitrogen contents, however the non protein nitrogen was double. A decrease of 19.1 and 20.6% in relation to total nitrogen was observed to the total globulin and albumin fractions, respectively. The gel filtration chromatography on Sepharose CL-6B and SDS-PAGE demonstrated alterations on the distribution patterns of the albumin and total globulin fractions between the initial and the sixth day of germination suggesting the occurrence of protein degradation in the germination process.The assay for acid protease only appeared in the albumin fraction with casein and chickpea total globulin as substrates, whereas the former was more degradated than the latter, however the transformations detected in the protein fractions apppear indicated that others enzymes could be acting during the process. The trypsin inhibitor activity had a little drop after six day of germination indicating a possible increase on the digestibility of the proteins.
Keywords: Chickpea; Cicer arietinum L.; Germination; Protein fractions; albuminoid; globulin; nitrogen; peptide hydrolase; sepharose; trypsin inhibitor; vegetable protein; chemistry; chickpea; cotyledon; enzymology; gel chromatography; germination; growth, development and aging; metabolism; plant seed; polyacrylamide gel electrophoresis; Albumins; Chromatography, Gel; Cicer; Cotyledon; Electrophoresis, Polyacrylamide Gel; Globulins; Nitrogen; Peptide Hydrolases; Plant Proteins; Seeds; Sepharose; Trypsin Inhibitors